COMPARISON OF PREMIUM RESERVES USING LEE-CARTER MODEL AND USA MORTALITY TABLE - SEBASTIAN YUNUS, EDWIN
Premium Reserve is the insurance company's obligation to pay a number of funds that must be prepared by the insurance company to pay the value of the benefits at the time of coverage. The calculation of premium reserves is driven by various factors, one of which is death probability. One of the methods to calculate the death probability with the Lee-Carter model. The Lee-Carter Model is a model that had been used to forecast the mortality rate on specific or certain region. In this research, stochastic mortality will be modelled using the Lee-Carter model. With this stochastic effect, the probability of death will be forecasted to be more precise because stochastic method considers the uncertainty factor. The death probability will be calculated using mortality data in the United States for the period 2019. This death probability will be used to calculate the premium and reserve value for 10-year term life insurance using Prospective reserve and Zillmer reserve. This also affects the reserve value using the Lee-Carter model which is lower than the USA mortality table.